(untitled) (Student’s Journal of Health Research Africa, 2022)
Background: The purpose of the study is to determine knowledge attitudes and practices toward the prevention of brucellosis among cattle keepers aged (15-to 45) years in Lyantonde general hospital Lyantonde district Methodology: The study design was a convenience sampling technique in nature and the researcher employed a simply Convenience sampling technique to select 50 study participants. The questionnaire was used as a data collection tool on a sample size of 50 respondents; data were analyzed manually using a scientific calculator by tallying, counting, and presented in a computer program to generate tables, graphs, and pie-charts Results: 96% have ever heard about brucellosis, 56% have heard of brucellosis from health workers, 70% know how brucellosis is spread, 64% know that raw milk can cause brucellosis, 70% know how to prevent brucellosis, 64% are aware that undercooked meat can cause brucellosis, 64% also know that contact with animal products can cause brucellosis and 66% know that animal by-products are the major risk factors, 74% have a positive attitude, 60% have the perception that brucellosis is a health problem, 70% have a perception that medical intervention can stop brucellosis spread, 96% take raw milk, 68% have ever tested for brucellosis, 52% have ever got in contact with the aborted fetus, 86% got in contact with any other animal products and 60% seek medical treatment from health facilities. Conclusion: The majority of the respondents have good knowledge and a positive attitude towards the prevention of brucellosis and poor practice. Recommendation: The ministry of health (MOH) should put guidelines on the proper handling of animal products and provide massive sensitization on the control and prevention of brucellosis.